Case Report: Successful DSA-guided removal of a fractured PICC catheter from the pulmonary artery in a patient with lung cancer - Lai, Jun; Xiao, Xue; Wen, Chunyan; Zhang, Yaoyu; Meng, Wenjun; Zheng, Rujun (Frontiers in Oncology, 2025)
BackgroundPeripherally inserted central catheters (PICCs) are widely used for long-term intravenous therapy, especially in cancer patients. Although generally safe, PICC-related complications such as catheter fracture and migration can pose serious risks.Case presentationWe report a case of a 41-year-old female with lung adenocarcinoma who developed PICC catheter fracture, with the broken segment migrating into the pulmonary artery during chemotherapy. The patient presented without significant symptoms, and imaging confirmed the intravascular migration of the catheter fragment. After multidisciplinary evaluation, the fractured catheter was successfully removed under digital subtraction angiography (DSA) guidance via a minimally invasive endovascular approach. The patient recovered uneventfully.ConclusionThis case highlights the rare but serious complication of PICC catheter fracture with subsequent migration into the pulmonary artery during chemotherapy in a patient with lung adenocarcinoma. Prompt identification and multidisciplinary management, including minimally invasive retrieval under DSA guidance, ensured a favorable outcome and avoided major morbidity. The experience underscores the importance of standardized PICC maintenance protocols, comprehensive training of nursing staff, and patient education on self-care to minimize preventable complications. Furthermore, our findings emphasize the need for regular catheter monitoring and timely intervention when abnormalities are detected. Minimally invasive endovascular techniques represent a well-documented, safe and effective alternative to traditional surgical methods for the retrieval of intravascular foreign bodies, with advantages of reduced trauma, faster recovery, and fewer complications. Continued efforts to enhance nursing skills, strengthen follow-up, adopt polyurethane catheters instead of silicone PICC per current guidelines, and promote patient awareness are essential to improve the safety and success rates of PICC utilization in cancer populations requiring long-term intravenous access.